Results and Problems in Cell Differentiation
DOI: 10.1007/400_2007_053
|View full text |Cite
|
Sign up to set email alerts
|

Biological Function of Prokineticins

Abstract: Secreted peptides have been implicated in diverse physiological functions. Prokineticins are a pair of regulatory peptides that signal through two highly homologous G protein-coupled receptors. Prokineticins possess a unique structural motif of five disulfide bonds and conserved N-terminal stretches. Diverse biological functions, ranging from development to adult physiology, have been attributed to prokineticins. Herein we provide an overview of current knowledge of this interesting pair of regulatory peptides. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Expression analysis of PKRs in heterogeneous systems revealed that they bind and are activated by nanomolar concentrations of both recombinant PKs, though PK2 was shown to have a slightly higher affinity for both receptors than was PK1 [12]. Hence, in different tissues, specific signaling outcomes following receptor activation may be mediated by different ligand-receptor combinations, in accordance with the expression profile of both ligands and receptors in that tissue [13]. Activation of PKRs leads to diverse signaling outcomes, including mobilization of calcium, stimulation of phosphoinositide turnover, and activation of the p44/p42 MAPK cascade in overexpressed cells, as well as in endothelial cells naturally expressing PKRs [5], [7], [8], [14], [15] leading to the divergent functions of PKs.…”
Section: Introductionmentioning
confidence: 88%
“…Expression analysis of PKRs in heterogeneous systems revealed that they bind and are activated by nanomolar concentrations of both recombinant PKs, though PK2 was shown to have a slightly higher affinity for both receptors than was PK1 [12]. Hence, in different tissues, specific signaling outcomes following receptor activation may be mediated by different ligand-receptor combinations, in accordance with the expression profile of both ligands and receptors in that tissue [13]. Activation of PKRs leads to diverse signaling outcomes, including mobilization of calcium, stimulation of phosphoinositide turnover, and activation of the p44/p42 MAPK cascade in overexpressed cells, as well as in endothelial cells naturally expressing PKRs [5], [7], [8], [14], [15] leading to the divergent functions of PKs.…”
Section: Introductionmentioning
confidence: 88%
“…Prokineticin 2 (PK2) is a multifunctional secreted regulatory peptide that signals through two G protein-coupled receptors termed prokineticin receptors 1 and 2 (PKR1 and PKR2) [12-14]. Emerging evidence indicates that PK2 is also associated with pain perception.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of prokineticin signaling has been elaborated in a number of diverse physiologic processes, including inflammation, haematopoeisis, angiogenesis, circadian rhythms, and reproduction (reviewed in Refs 7,15,16 …”
mentioning
confidence: 99%